(untitled) (IAHS Medical Journal, 2023)
Background: Regional anaesthesia has become an important anaesthetic technique now a days. The use of spinal anaesthesia is often limited by the unwillingness of patients to remain awake during surgery. Pharmacologically induced tranquility improves acceptance of regional technique. This study compares Clonazepam and Diazepam in terms of onset and recovery of sedation, haemodynamic effects and adverse effects of both the drugs during elective caesarian section under spinal anaesthesia. Materials and methods: This randomized clinical trial included 60 ASA (American Society of Anaesthesiologists) grade I patients between age 20-40 years undergoing elective Caesarean sections under spinal anaesthesia during the period of January 2022 to June 2022. Patients were randomly allocated to one of two groups: Clonazepam group (Group C, n=30), who received Clonazepam in a single dose of 0.015mg/kg and Diazepam group (Group D, n=30), who received Diazepam in a single dose of 0.15mg/kg. Results: There was no significant difference of mean blood pressure and mean heart rate between the two groups (p>0.05). Time of onset and duration of sedation was comparable between the two groups (p value 0.759 and 0.652 respectively). Percentage of patient satisfaction was comparable between the two groups(80% vs 86.66%, p value 0.841). Incidence of pain in arm during drug administration was significantly more in Diazepam group (10% vs 100%, p<0.001). Conclusion: Both Clonazepam and Diazepam have satisfactory haemodynamic stability and sedation characteristic in single dose technique during spinal anaesthesia for caesarean section. IAHS Medical Journal Vol 5(2), Dec 2022; 20-24